Lesbians, Drag Kings, and Pregnant Queens: The Digby Mary Magdalene’s Queer Relationships - Black, Daisy (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This article argues that the Digby Mary Magdalene’s biblical, hagiographical, and allegorical characters support performance registers that provide a fertile space for queer relationships to emerge. It begins with Mary’s seducer, the lesbian-like Lady Luxuria, whose amiable tongue follows patterns more common to heterosexual seduction scenes. It then examines the Gallant’s parodic man-about-town, who wears courtly love as insincerely as his tight clothing and anticipates the flamboyant gender performances of modern drag kings. The article examines the lingering implications of these interactions on Mary’s post repentance plot with the Queen of Marseilles and on the play’s medieval and modern audiences.